Studies on the Biology and Habits of the Maize Stalk Borer Sesamia cretica Lederer (Lepidoptera, Noctuidae) - AHMED, MOSTAFA KAMAL (The Libyan Journal of Agriculture, 2023)
The adult and immature stages of the maize stalk borer, Sesamia cretica Led. were described. Eggs are laid in clusters which contain an average of 18.2 eggs per cluster. They hatch after 4.6 days on the average. The larva has six instars which average 4.0, 3.7, 3.4, 3.5, 3.8, and 10.2 days respectively. Larvae transfer to pupae inside delicate coccoons between plant leaves or in earthern cells in the soil. Adults emerge after an average of 11.2 days; and a generation is completed in 44.4 days on the average. All larval instars can feed inside the whorls of grown plants. Boring starts in the third instar; but the last three instars are the true borers. Afpanteles ruficrus Haliday parasitizes the fourth instar of borer larvae during June and July. About 14 37 parasites develop in each host.